Melampaui Kompetensi Guru: Pelatihan Guru Sebagai Prediktor Kualitas Pembelajaran Di Madrasah Indonesia - Siti Nurhayati; Hari Nugraha; Widayanto Widayanto (JENTRE, 2026)
Despite extensive evidence that teacher training enhances teacher competence, empirical studies linking training directly to learning quality remain limited, particularly in Islamic school settings. This study examines the relationship between teacher training quality and learning quality among English teachers in Indonesian madrasahs. Using a quantitative explanatory design, data were collected from 59 English teachers who participated in technical and functional training programs organized by the Ministry of Religious Affairs between 2016 and 2019. Participants were selected through proportional stratified random sampling from a population of 147 training alumni. Teacher training quality was measured through six dimensions: training duration, participant characteristics, instructional methods, trainer competence, facilities, and training materials. Learning quality was assessed across five dimensions: relevance, attractiveness, effectiveness, efficiency, and productivity. The findings reveal a significant positive relationship between teacher training quality and learning quality (R = 0.641, p < 0.001), with training explaining 41% of the variance in learning quality (R² = 0.410). The strongest effect was observed on learning efficiency (R² = 0.376), whereas the weakest effect was found on learning attractiveness (R² = 0.215). These results suggest that teacher training contributes not only to professional development but also to improvements in classroom learning quality. This study extends the professional development literature by demonstrating that the effects of teacher training can be traced beyond teacher competence to multiple dimensions of learning quality. The findings underscore the importance of expanding access to high-quality teacher training as a strategy for improving educational quality in madrasahs.